Analisis Faktor Penyebab Rendahnya Hasil Belajar Peserta Didik Kelas V Pada Mata Pelajaran Matematika - Misyanto Misyanto (Anterior Jurnal, 2016)
This study aims to determine the factors causing low learning outcomes of students in the fifth-grade mathematics class V SD Muhammadiyah Pahandut. The approach used in this study is a qualitative approach with a case study. Data collection techniques used in this research is observation, interview, and documentation. Subjects consisted of 8 students, 1 teacher of Mathematics and Head of School. Results of this study are : (1) The internal factors, lack of interest and motivation of learners during the learning of Mathematics ; (2) External factors, methods of teaching and teachers who did not appeal to learners.